A Comparative Multimodal Analysis on Selected Advertisements: Lays & Pringles - Prastiwi, Almeida; Bramantya Pradipta (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2024)
Advertisement is a type of communication that aims to promote or provide information about products, services, or ideas to the general public to influence their actions or views, the purpose of advertisements is to increase sales, build brand awareness, and inform that there is a new product. Using the multimodal theory from Anstey & Bull (2010) which is semiotic system, this research finds out the semiotic system on Lays and Pringles advertisements and the similarities and differences of semiotic system on Lays and Pringles advertisements. The part that will be analyzed is the comparative of semiotic system on Lays and Pringles advertisements. This study, employed qualitative method and using table to compare the semiotic system that exists in Lays and Pringles advertisements. The data were taken from scenes in Lays and Pringles advertisements on YouTube. Semiotic system that exists in Lays and Pringles based on theory of Anstey & Bull (2010) is linguistic analysis, visual analysis, audio analysis, gesture analysis, and spatial analysis. The total of findings from this study is 48. In the two advertisements that have been researched, all semiotic systems including 15 linguistic analysis, 10 visual analysis, 11 audio analysis, 9 gesture analysis, and 3 spatial analyses. The result show that there are five aspects of semiotic systems based on Anstey & Bull (2010) theory. All similarities and differences also appear except the audio analysis. The similarities of audio analysis did not appear because the two advertisements have been using different music for the audio. Keywords: Comparative, Lays, Multimodal, Pringles, Semiotic System.